Unnat Bharat Abhiyan, A Government of India Initiative Complementing Service Learning in Engineering - Bandi, Surendra; Naik, Santosh Madeva (Journal of Engineering Education Transformations, 2021)
Education is one of the most important priorities for any country and Government of India has been implementing several initiatives to take education to every part of the nation. Several objectives like increasing literacy rate, improving quality of education, encouraging skillbased education, promoting technical education, supporting innovations, and empowering universities, were on the top list and made a significant progress over the years. The initiatives of the government were generally open for government institutions and premium private institutions. The most important part of education is to stay connected with society. The education curriculum did not offer much scope to connect with society at large. This article brings out the experience of HITAM(Hyderabad Institute of Technology and Management), an engineering college which benefitted from the government initiative â€œUnnat Bharat Abhiyanâ€(UBA). HITAM has been a Participating Institution of UBA since 2018. The initiative helped faculty and students to work with society, understand the societal development, know the role of engineer for the society, take up technological interventions and develop products used in the society. This in turn created a platform for students to apply engineering knowledge in real time problems. Being a participating institution, HITAM followed the framework of UBA and adopted five villages, conducted household survey, organized gram sabhas, identified the problems in the adopted villages where technological interventions are required. The proposals for technological interventions were uploaded in UBA portal and were scrutinized by the subject expert groups. The college was sanctioned with the required budget to carryout the projects proposed. Surendra Bandi Department of Computer Science & Engineering, HITAM, Hyderabad surendra.mca@hitamorg More than 100 students took part in the village surveys and 18 students were part of technological interventions. HITAM received fund from the Government for conducting household survey, technological interventions and perennial funding for active involvement in all the UBA activities. The students who were part of the initiative expressed that it was a life changing experience for them towards society and complemented their learning. Service-learning as a pedagogy was evolved out of the initiative at HITAM, apart from the financial support from the Government.